2017
DOI: 10.5194/hess-2017-532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing micro watershed management for soil erosion control under various slope gradient and vegetation cover conditions using SWAT modeling

Abstract: Abstract. This study evaluated parameters of soil erosion and optimization of micro watersheds by applying a semidistributed basin-scale Soil and Water Assessment Tool (SWAT) model in various small watersheds of the Chakwal and Attock districts of Pothwar, Pakistan. The model was calibrated and validated on a daily basis for a small catchment (Catchment-25) of the Dhrabi watershed without any soil conservation structures. Statistical measures (R2 and EN-S) were used to evaluate model performance; the model per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
2
Order By: Relevance
“…Due to its strong sediment yield component, SWAT could be used to extrapolate sediment distribution throughout the catchment, identify vulnerable areas and promote best management practices. As such, it is considered a more suitable tool for agricultural management practices in watersheds of varying sizes, compared with other models (Nabi et al, 2017).…”
Section: Sediment Yield Modelling Using Swatmentioning
confidence: 99%
“…Due to its strong sediment yield component, SWAT could be used to extrapolate sediment distribution throughout the catchment, identify vulnerable areas and promote best management practices. As such, it is considered a more suitable tool for agricultural management practices in watersheds of varying sizes, compared with other models (Nabi et al, 2017).…”
Section: Sediment Yield Modelling Using Swatmentioning
confidence: 99%
“…No caso da vulnerabilidade natural à perda de solos, há diversas propostas metodológicas conhecidas, sendo uma das mais difundidas a Equação Universal da Perda de Solos, ou simplesmente USLE (Wischmeier;Smith, 1978;Alewell, 2019), como é conhecida na sigla em inglês. Como o próprio nome diz, ela se propõe a estimar a perda média de solos pela erosão em vertentes, consistindo em um modelo empírico de estimativa da erosão laminar (Nabi et al, 2017;. A USLE também tem sido utilizada em trabalhos que se propõem a mapear a vulnerabilidade ambiental, a exemplo de Ribeiro et al (2016) e Souza et al (2019).…”
Section: Issn:1984-2295unclassified
“…On the other angle, steep slopes (N 15°) showed high prevalence of soil loss. Similarly, Nabi et al (2017) suggested that soil and water conservation measures targeting steep slopes significantly reduce soil loss at watershed level. This implies that comprehensive soil conservation measures should be developed to control erosion on steep slopes and prevent sediment delivery to rivers (Haiyan and Liying, 2017;Gashaw et al, 2017).…”
Section: Implications For Sustainable Land Management and Soil Consermentioning
confidence: 99%